2016
DOI: 10.11648/j.ajbls.20160403.13
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Catabolism in Adult <i>Onchocerca volvulus:</i> An Immunohistochemical Study

Abstract: Abstract:Onchocerca volvulus is a parasite responsible for Onchocerciasis whose main pathology is blindness. Existing treatment and control approaches are not entirely successful, with some, fraught with safety challenges. Due to these problems, the need for developing safer and effective drugs to combat the disease has become imperative. However O. volvulus materials are restricted by ethical concerns due to its strict human preference. To overcome these concerns some researchers use animal models of closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…It is however possible, that amidase might not be a chokepoint enzyme. Hence, the worms could switch to alternative metabolic pathways [17] which does not require amidase and might thus increase their survivability in vitro, thereby accounting for the observed enhancement in worm motility scores in this study. It was further observed that the control group which had only medium showed the worst motility score from day 3 onward.…”
Section: Volvulus Over the Course Of 8 Days Of Culturementioning
confidence: 77%
See 2 more Smart Citations
“…It is however possible, that amidase might not be a chokepoint enzyme. Hence, the worms could switch to alternative metabolic pathways [17] which does not require amidase and might thus increase their survivability in vitro, thereby accounting for the observed enhancement in worm motility scores in this study. It was further observed that the control group which had only medium showed the worst motility score from day 3 onward.…”
Section: Volvulus Over the Course Of 8 Days Of Culturementioning
confidence: 77%
“…Therefore, the search for a microfilaricide and alternative drugs against onchocerciasis remains a top research priority (Seidu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation